PENGUATAN EKONOMI MASYARAKAT DESA MELALUI EKONOMI KREATIF BERBASIS ECOFRIENDLY DI DESA SULANGAI, PETANG, BADUNG - Yasintha, P.N.; Wirantari, I.D.A.P.; Adityananda, M.; Pramana, G.I. (Buletin Udayana Mengabdi; Vol 20 No 3 (2021): Buletin Udayana MengabdiDO - 10.24843/BUM.2021.v20.i03.p13, 2022)
The tourism industry is the driving force behind the province of Bali's economic growth. Tourism development, on the other hand, is still concentrated in southern Bali. This leads to economic inequity in Bali's province. Sulangai Village is one of the villages in Badung Regency, Bali Province, that has begun to build its economy by using ecotourism as a means of improving its people's economic situation. However, many people in Sulangai Village continue to rely only on agriculture as a source of income due to the village's limited tourism opportunities. Village development must also be backed up with a reliable source of village income. To be able to create the economy from the smallest level, namely the family, various strata of the village community must be empowered. This will be attempted to be implemented in the form of community-based science and technology service activities. The village administration of Sulangai plays an essential role since, as a result of local autonomy, the village is no longer the aim of development but the development itself. As a result, the activity's goal is to stress community empowerment by teaching the concept of a creative economy based on environmental sustainability. This activity plan will also include plans for the creation of Village-Owned Enterprises and cooperatives as a way for locals to put their empowerment into action and become a driving force in Sulangai Village's economy. Then, in order for this action to have a substantial influence, it is required to examine the Village Medium-Term Development Plan (RPJMDes) and have it implemented in the following year's village revenue and spending budget.